Does the currency changeover to euro rise prices? An experimental study from Czech Republic. - Bohumínský, Roman; Koten, Silvester van, 1970-; Zajíček, Miroslav, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
In the euro area, the changeover to the euro was accompanied by fears of increases in prices by consumers. However, in most countries the changeover had barely any effect on inflation indices, but a significant effect on perceived inflation and even now people still believe that the price increase was more dramatic than it was in reality. This paper examines the situation in the Czech Republic, being one of the last countries in the EU which have not adapted the euro yet. I am especially interested in finding whether a changeover would lead to price increases even though Czech citizens have got plenty of time to indirectly familiarize with the euro currency. The analysis is based on a laboratory experiment. With this method I am studying the effects of transition to euro on consumer behavior. In addition, I compare the results (indirectly) with those of other European countries. Under the framework of posted price experiment, it can be concluded that, in the particular sample, the changeover to euro currency does in fact affect the outcome of trade at least temporarily. In this case, the changeover from CZK to EUR leads to elevation of prices and reduction of the traded quantities, especially right after the changeover. The main reason for this is that the producers (sellers) tried to exploit the changeover situation in order to increase their profits. All the presented results are significant at 5% level.
Vedoucí práce: Silvester van Koten
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses